Levinas and Literature : New Directions. - Fagenblat, Michael. (Perspectives on Jewish Texts and Contexts Series, 2020)
This series focuses on the Jewish textual tradition as well as the ways it evolves in response to new intellectual, historical, social and political contexts. Fostering dialogue between literary, philosophical, political and religious perspectives, this series, which consists of original scholarship and proceedings of international conferences, reflects contemporary concerns of Jewish Studies in the broadest sense.